-z=-7-8z

Simple and best practice solution for -z=-7-8z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -z=-7-8z equation:


Simplifying
-1z = -7 + -8z

Solving
-1z = -7 + -8z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '8z' to each side of the equation.
-1z + 8z = -7 + -8z + 8z

Combine like terms: -1z + 8z = 7z
7z = -7 + -8z + 8z

Combine like terms: -8z + 8z = 0
7z = -7 + 0
7z = -7

Divide each side by '7'.
z = -1

Simplifying
z = -1

See similar equations:

| -13x+38=6x-25 | | x^2-kx+1=0 | | 2x+5=2(x-1) | | 2.2x-5=8x+3 | | 3(b+4)=(b+4)2 | | -4x-7=12 | | =2x-8xy | | 4/21-h/24 | | 2x+2-2(-5x-5)=2(x-3) | | 6a-4b+a-5b= | | 6t+16=9 | | 1/5/1 | | (3/4)t+(1/8)=(3/4)(t+8) | | m/4=9/5 | | -1/5/-1 | | 6+16=9 | | 20=-2v | | -2x=-2+5 | | 0=-6n-2n | | 2x+9-2=31 | | 4.4x+64=19.36+8x | | x+(3x^1/2)-10 | | 2+6d-4= | | 9/11*14.4=-12 | | 4(x+2)-6=2x | | -4=6b-4+2b | | 9/2d=27 | | m/4=h/24 | | s+2/1/2s+10=31 | | 9(2/3) | | -x-24=-8 | | 20+5n=6n-3(n-4) |

Equations solver categories